Updating of data through atomic ring Model in Big data - Kirubanantham, P.; Jeeva, C.; Sheena, B. Gracelin (International Journal of Psychosocial Rehabilitation, 2020)
Big data is the collection of huge data that is been transacted and analyzed in day to day basis. Data analysis is the huge task to be manipulated in time to time basis. Updating and prediction of data is the uphill task and it is a greatest challenge to provide a updated information to the user. Atomic ring based pattern will provide a differentiation between old data and updated data among the data to the user. Pruning process will remove the older data when the new data gets updated.